OPTIMALISASI PERAN PENYULUH PERTANIAN LAPANGAN (PPL) TERHADAP PEMBERDAYAAN KELOMPOK TANI HORTIKULTURA - Fernanda Chesaridestiwany (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The agricultural sector plays a strategic role in Indonesia's economic development, particularly in supporting food security and improving the welfare of rural communities. Field Agricultural Extension Workers (PPL) play a crucial role in assisting and empowering farmers. However, the limited number of extension workers, the low quality of extension services, and the lack of farmers' trust pose significant challenges in optimizing the role of PPL. This study aims to identify the priority roles of PPL in supporting the empowerment of horticultural farmer groups in Parindu District, Sanggau Regency, where the PPL-to-farmer group ratio is 1:18. The method used is the Analytic Hierarchy Process (AHP), involving respondents from various stakeholders, including PPL, farmer group leaders and members, village government officials, and the agricultural office. The results show that the highest priority role of PPL is as a facilitator (weight 0.399), with a primary focus on facilitating access to financing and capital, particularly government capital assistance. The role of educator ranks second (weight 0.323), followed by motivator (weight 0.192), and organizer (weight 0.086). These findings highlight the importance of strengthening the facilitation capacity of PPL to enhance the empowerment of horticultural farmer groups. The recommendations of this study are expected to serve as a basis for improving the agricultural extension system in a more practical and targeted manner at the local level.